Injury death in são josé do rio preto-1996-1998 - D’ Avila, Antonio M. M. Pires; Oliveira, Augusto B.; Goldbaum, Moisés (Medicina (Ribeirao Preto), 2004)
Introduction: An epidemiological study of the mortality rates by injuries in São José do Rio Preto, State of São Paulo, Brazil, has been carried out. The period considered is 1996-1998. Objectives: To show injuries mortality rates in São José do Rio Preto-SP in 1996-98. Methods: The study was based on official data from the Mortality Information Service of the Brazilian Ministry of Health, and in a survey based on data from medical forensic examiners (IML).Software Epinfo6.0 and Tabwin was utilized for data analises. Results:The results were compared to values obtained in the literature for the other cities of São Paulo and Brazil. In the case of São José do Rio Preto, was observed a decrease in the number of deaths associated with external causes in the period, but particularly in deaths due to traffic accidents with motor vehicles an increase in cases of pedestrians killed by hit-and-run drivers, that is much larger than the corresponding values for Brazil and for the State of São Paulo. The study showed increase in rates of homicides, mainly in the 15 to 39 years age group . Conclusion: This result suggests that is important to start programs to reduce the number of deaths by injuries, as well as the necessity of monitoring locally all these data.